Cardiac magnetic resonance predictors of readmission for heart failure in elderly vs not elderly patients after ST-segment elevation myocardial infarction. (3rd October 2022) - Merenciano-Gonzalez, H; Marcos Garces, V; Gabaldon-Perez, A; Gavara, J; Lopez-Lereu, M P; Monmeneu, J V; Perez, N; Rios-Navarro, C; De Dios, E; Chorro, F J; Valente, F; Lorenzatti, D; et al.
Abstract: Background: Patients with ST-segment elevation acute myocardial infarction (STEMI) have an increased risk of re-admission for acute heart failure (AHF). However, identification of patients at higher risk of AHF is challenging, especially in elderly individuals. The implications of cardiac magnetic resonance (CMR) imaging soon after the acute event for this specific purpose are unknown. Purpose: We aim to study the clinical and CMR predictors of AHF in elderly and not elderly patients after STEMI. Methods: STEMI patients treated with percutaneous coronary intervention and discharged from three university hospitals were included in a multicenter registry. We registered baseline clinical characteristics, echocardiographic parameters and early (1-week) CMR parameters - left ventricular ejection fraction (LVEF, %), infarct size (% of left ventricular mass) and microvascular obstruction (MVO, number of segments). Univariate and multivariate comparisons were performed in elderly (>70 years) and not elderly (≤70 years) patients to predict AHF during follow-up. Results: The cohort was comprised of 759 patients, of which 177 (23.3%) were elderly (>70 years). During a mean follow-up of 5.23±3.54 years, 79 (10.4%) patients presented AHF. In not elderly patients, Killip class at admission (HR 2.05 [1.32–3.17], p=0.001), anterior infarction (HR 3.43 [1.13–10.36], p=0.03) and CMR-LVEF (HR 0.94 [0.91–0.98] per increased %, p=0.001) independently predicted AHF. However, a combined risk score comprising these variables was not superior to CMR-LVEF alone to predict AHF during follow-up (AUC 0.81 [0.74–0.88] vs. 0.81 [0.73–0.88], p=NS). In elderly patients, CMR-LVEF was the only predictor of AHF in the final multivariable model (HR 0.94 [0.91–0.97], p<0.001), although its predictive power was moderate (AUC 0.68 [0.56–0.80], p=0.001). Most AHF events in the not elderly subgroup occurred in patients with reduced (≤40%) CMR-LVEF (71%), while in the elderly subgroup AHF occurred more frequently in patients with preserved (≥50%, 30%) or mildly reduced (40–49%, 32%) CMR-LVEF than reduced (≤40%) CMR-LVEF (38%). Conclusions: LVEF quantified by CMR soon after STEMI can accurately predict the risk of AHF in not elderly (≤70 years) patients and identify those individuals at higher risk (i.e. CMR-LVEF ≤40%). However, in elderly (>70 years) patients most AHF occur in patients with CMR-LVEF >40%, emphasizing the need for better predictive strategies in this population. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Instituto de Salud Carlos III and "Fondos Europeos de Desarrollo Regional FEDER" and Conselleria de Educaciόn – Generalitat Valenciana.